Pengaruh Machiavellian dan Religiusitas terhadap Niat Melakukan Whistleblowing - Gisca Inayah Yudira; Herlina Helmy (Universitas Negeri Padang, 2024)
This research intends to examine the impact of Machiavellianism and religiosity on whistleblowing intentions. This research is quantitative. This research used a purposive sampling method with 201 respondents from 25 SKPD in Sijunjung Regency. This data was analyzed using multiple regression analysis in SPSS version 23. The first variable is Machiavellian which has a negative effect on whistleblowing intentions, where t count is 2.072 > t table 1.974 at sig,0.040 < 0.05. The second variable is religiosity has a positive effect on whistleblowing intentions, where tcount is 2.096 > t table 1.974 at sig 0.038 <0.05.